Peran Bank Sampah Dalam Meningkatkan Pendapatan Masyarakat Belawan - Bakhtiar Efendi; Imelda Krisdamayati; Yolanda Widya; Anwar Suhut (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Waste banks are blessed with processing. This processing has the aim of making waste into products that can be sold and gain economic value. Yayasan gugah nurani indonesia is a non-governmental humanitarian organization that works in accordance with the pillars of the SDGS (Sustainable Development Goals), especially in areas related to children's rights and community empowerment. Gugah nurani indonesia is a legal foundation under the decree of the minister of law and human rights number: ahu-594.ah.01.04. On February 24, 2009. Gugah nurani indonesia is an incorporated foundation under the decree of the minister of law and human rights number: ahu-594.ah.01.04. On February 24, 2009. The blessing waste bank has some waste management outside the waste bank. This management is the management of organic waste which is made into compost from the results of the compost is also sold by the waste bank to consumers who need it. Based on the results of the study, it shows that customers have a major contribution to improving the waste bank economy. In this study, the results of customer activeness from the blessing waste bank related to customer activeness in the waste bank are very good. Educating the community by providing knowledge related to waste and providing training. Providing guidance and support to customers by facilitating customers so that customers can become independent and able to create their own creativity.